Glycemic control in diabetic children and adolescents after attending diabetic camp - Erwin P. Soenggono; Rara Purbasari; Aman B. Pulungan; Bambang Tridjaja (Indonesian Pediatric Society, 2011)
Background Type 1 diabetes mellitus (T1DM) is an emerging disease worldwide. Glycemic control in pediatric T1DM patients is a challenge in diabetes management. Attending diabetic camp has been associated with improved glycemic control in diabetic children and adolescents.Objective To determine the effect of diabetic camp attendance on glycemic control in children and adolescents with T1DMMethods A cross-sectional, non-experimental study was done in December 2010 at a diabetic camp held in Bogor, Indonesia. The two-day camp educated diabetics about T1DM, including insulin use, meal planning, exercise, monitoring and complications. The diabetic camp was attended by 28 children and adolescents, consisting of 5 boys and 23 girls, aged 7 – 18 years. Eighteen participants completed the requested data for our study. Glycosylated hemoglobin (HbA1c) was measured before and 3 months after subjects attended the camp. Participants also filled the Pediatric quality of life (PedsQL) questionnaire. We compared HbA1c levels before camp and 3 months after, by Stata 19.Results Before camp, the mean HbA1c was 9.18% (SD 2.48) and 3 months after camp it was 8.67% (SD 1.62), a statistically significant improvement (P=0.004). The PedsQL revealed that none of the subjects had poor quality of life.Conclusion Glycemic control in T1DM children and adolescents was significantly improved 3 months after attending diabetic camp compared to that before attending camp. According to subjects’ self-assessment by PedsQL questionnaire, no subjects indicated a poor quality of life for the duration of their illness. [Paediatr Indones. 2011;51:294-7].